Common Bean Productivity and Micronutrients in the Soil–Plant System under Residual Applications of Composted Sewage Sludge - Oliveira, Gabriela Souza de [UNESP]; Jalal, Arshad [UNESP]; Prates, Adrielle Rodrigues [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP]; Alves, Rodrigo Silva [UNESP]; Silva, Luana Corrêa [UNESP]; Nascimento, Raimunda Eliane Nascimento do [UNESP]; Silva, Philippe Solano Toledo [UNESP]; Arf, Orivaldo [UNESP]; Galindo, Fernando Shintate [UNESP]; Oliveira, Fernando Carvalho; Abreu-Junior, Cassio Hamilton; et al. (MDPI, 2023)
Composted sewage sludge (CSS) is an organic fertilizer that can be used as a source of micronutrients in agriculture. However, there are few studies with CSS to supply micronutrients for the bean crop. We aimed to evaluate micronutrient concentrations in the soil and their effects on nutrition, extraction, export, and grain yield in response to CSS residual application. The experiment was carried out in the field at Selvíria-MS, Brazil. The common bean cv. BRS Estilo was cultivated in two agricultural years (2017/18 and 2018/19). The experiment was designed in randomized blocks with four replications. Six different treatments were compared: (i) four increasing CSS rates, i.e., CSS5.0 (5.0 t ha−1 of applied CSS, wet basis), CSS7.5, CSS10.0, CSS12.5; (ii) a conventional mineral fertilizer (CF); (iii) a control (CT) without CSS and CF application. The available levels of B, Cu, Fe, Mn, and Zn were evaluated in soil samples collected in the 0–0.2 and 0.2–0.4 m soil surface horizons. The concentration, extraction, and export of micronutrients in the leaf and productivity of common beans were evaluated. The concentration of Cu, Fe, and Mn ranged from medium to high in soil. The available levels of B and Zn in the soil increased with the residual rates of CSS, which were statistically not different from the treatments with CF. The nutritional status of the common bean remained adequate. The common bean showed a higher requirement for micronutrients in the second year. The leaf concentration of B and Zn increased in the CSS7.5 and CSS10.0 treatments. There was a greater extraction of micronutrients in the second year. Productivity was not influenced by the treatments; however, it was higher than the Brazilian national average. Micronutrients exported to grains varied between growing years but were not influenced by treatments. We conclude that CSS can be used as an alternative source of micronutrients for common beans grown in winter.
Keywords: food security; organic fertilizers; Phaseollus vulgarisL; plant nutrition; urban waste